John Lewis Gaddis: The Cold War: A New History. (Czech Journal of International Relations, 2006)
John Lewis Gaddis: The Cold War: A New History. 1st ed. New York: The Penguin Press, 2005, 333 stran, ISBN 1-59420-062-9.